ICT policy and regulation in Malaysia / Sharazad Haris, Saadiah Yahya and Wan Aryati Wan Ghani - Haris, Sharazad; Yahya, Saadiah; Wan Ghani, Wan Aryati (Centre for Media and Information Warfare Studies, 2009)
The several phases of economic transformation with each phase resulting in increased job and wealth creation enables Malaysians to attain higher standards of living